Development of Culturally Responsive Teaching Approach Teaching Module Based on Ethnomathematics of The Kasepuhan Cirebon Palace - Karimah, Nurul Ikhsan; Erawati, Turini; Setiyani, Setiyani; Nasir, Fuad; Sundawan, Moh. Dadan; Setiawan, Arief Maulana; Sumarwati, Sri (International Journal of Educational Research Excellence (IJERE), 2025)
Teaching modules are one of the important aspects for teachers to design learning that supports students in achieving learning outcomes and learning objectives based on student characteristics. Mathematics learning is one of the most important subjects in elementary school education. Learning carried out by teachers is currently still monotonous by relying on textbooks and LKS, so that students do not know the relevance of learning, especially the culture of the Kasepuhan Palace. The type of research model used in this research method is using the ADDIE development model (Analysis, Design, Development, Implement, and Evaluate). The research was conducted at SDN Kesenden in the 2024/2025 academic year with research subjects of 21 grade IV students on the material of flat shape decomposition. Data collection techniques in the research on the development of teaching modules with the Culturally Responsive Teaching (CRT) approach. Data collection techniques in the research on the development of teaching modules with the Culturally Responsive Teaching (CRT) approach, researchers used Observation, Questionnaires, and Tests based on the ethnomathematics of the Kasepuhan Palace. The results of the validation of the teaching module showed very satisfactory results with a percentage of 90%, so this module was considered very valid. The results of the practicality test involving student responses produced a percentage of 88%, which was categorized as very practical. The effectiveness test of the module based on the learning completion of 21 students reached a percentage of 64.38%, which met the effective criteria. These findings indicate that the developed teaching module is able to support learning in a valid, very practical, and effective manner.